The TRRL high-speed road monitor : assessing the service ability of roads, bridges and airfields - 229031 Cooper, D. R. C.; Transport and Road Research Laboratory (Great Britain) (Crowthorne, Berkshire : Transport and Road Research Laboratory, 1985)
08